DRY HOLE ANALYSIS OF EXPLORATION WELLS IN MUARA SUBBASIN, GREAT TARAKAN BASIN, NORTH BORNEO - Gantifa Andwitri, Prayolandini
Muara Subbasin is a passive margin dominated by carbonate rocks. This basin is part of Great Tarakan Basin located in the offshore northeast of Borneo Island. Exploration in Muara Subbasin started in 1973 with seismic acquisition and continued with the drilling of three exploration wells until 1994. All wells, however, are plugged and abandoned due to no hydrocarbon accumulation. Exploration wells have indicated presence of hydrocarbon, which marked an active petroleum system in the area. This research aims to determine the cause of dry hole in this subbasin. This research used data literature, 59 2D seismic sections, and three wells which is Well Tanjung Batu-1 from 0 m to 1838 m, Well Tabalar-1 from 175 m to 2221 m, and Well Karang Besar-1 from 94 m to 3525 m. Well data consisting of logs (checkshot, dt, gr, density(rhob), neutron(nphi), and resistivity), porosity RCAL, lithology description from cutting, biostratigraphy, and hydrocarbon shows. Methodology used in this research included sequence stratigraphy analysis, petrophysical analysis, seismic facies analysis, and dry hole analysis. Integrated analysis of seismic, well, and data literature was conducted to analyze stratigraphic sequences. Source rock was interpreted based on literature and seismic data to produce the hydrocarbon kitchen map. Physical rock properties of each sequence were analyzed by petrophysics method followed by integrating it with RCAL porosity and hydrocarbon shows. By doing that, it can determine reservoir and seal sequence in the area. Mapping of depth structure map and isopach map were carried out in reservoir sequence. Facies analysis were interpreted based on seismic reflection parameters on reservoir sequence and seal. Integration of depth structure map, isopach, seismic facies, and lithological information in the cutting produced the gross depositional environment map of reservoir and seal interval. Tectonic activity analysis and structural interpretation were used to interpret critical moment and migration route of the hidrocarbon. The integrated study in each those elements was undertaken to interpret the cause of the absence of hydrocarbon accumulation, also known as dry hole analysis. This research concludes there are 11 sequences in Muara Subbasin. Sequence 1 is source rock sequence that can be found in the whole subbasin. Source rock in this subbasin have been oil generative since Late Miocene for the wells and over the period Late Oligocene through the present day for specific depocenters. Well Tanjung Batu-1 has indication of hydrocarbon shows in several sequences, but based on integration with petrophysical analysis, sequence 7 (Middle Miocene) is the most potential reservoir sequence. The trap is stratigraphic which is shelf margin build-up with fault as migration route of hydrocarbon from source rock. Critical moment occurred around Pliocene-Recent. Lithology of bottom sequence 8 (Middle Miocene) is still dominated with reef which isnot effective to became seal rock, resulted in no hydrocarbon accumulation in Well Tanjung Batu-1. Well tabalar-1 also has indication of hydrocarbon shows in several sequences, but based on integration with petrophysical analysis, sequence 7 (Middle Miocene) is the most potential reservoir. The lithology is dominated by calcarenite limestone. Top trap is stratigraphic which is shoal with fault as migration route of hydrocarbon from source rock. Critical moment occurred around Pliocene-Recent. Lithology of bottom sequence 8 (Middle Miocene) is still dominated with calcarenite limestone which isnot effective to became seal rock, resulted in no hydrocarbon accumulation in Well Tabalar-1. Karang Besar-1 that located basinward only has hydrocarbon indication around fault. The lithology is dominated with mudstone which is impermaeable and has no potential to become the reservoir rock.